Social media's dark side in online radicalisation - Noor Huda Ismail (2024)
Online radicalisation is a complex issue characterised by the different roles of digital propagandists and potential perpetrators, as highlighted by the recent security threats surrounding the Pope’s visit to Indonesia. To combat this threat effectively, we need to prioritise real-time monitoring and interdisciplinary collaboration, utilising AI tools to analyse and mitigate extremist content while advocating targeted interventions instead of punitive measures. Addressing radicalisation necessitates collective societal action and significant investment of relevant resources.